Direct H abstraction by molecular oxygen from unsaturated C3–C5 hydrocarbons: A theoretical study. Issue 3 (22nd December 2021) - Alarcon, Juan F.; Mebel, Alexander M.
Abstract: Potential energy surfaces for the H abstraction reactions by molecular oxygen from unsaturated closed‐shell C3–C5 hydrocarbons, including allene and propyne (C3 H4 ), propene (C3 H6 ), diacetylene (C4 H2 ), vinylacetylene (C4 H4 ), 1, 3‐butadiene (C4 H6 ), butene isomers (C4 H8 ), cyclopentadiene (C5 H6 ), and cyclopentene (C5 H8 ), which were earlier identified among the main pyrolysis products of jet fuel components, have been explored at the CCSD(T)‐F12/cc‐pVTZ‐f12//ωB97XD/6‐311G** + ZPE(ωB97XD/6‐311G**) level of electronic structure theory. The results of the ab initio calculations were then utilized in transition state theory calculations of the reaction rate constants. The H abstraction reactions by O2 appeared to be most favorable from the allylic sites and from allene and propyne forming the propargyl radical, with the reactions involving the cyclic allylic sites in cyclopentadiene and cyclopentene exhibiting the lowest reaction endothermicities and barriers. They are followed by the reaction of O2 with cyclopentene producing cyclopent‐1‐en‐4‐yl and the reactions with vinylacetylene and 1, 3‐butadiene forming the resonantly stabilized i ‐C4 H3 and i ‐C4 H5 radical products. The H abstractions from primary and secondary vinylic sites as well as from acetylenic sites are significantly less favorable and unlikely to compete. The calculated rate constants have been validated against the previous experimental and theoretical results for propene and butene isomers. All considered reactions of H abstraction by O2 are predicted to be rather slow, with their rate constants at 1500 K being on the order of 10 –17 ‐10 –16 cm 3 molecule –1 s –1 and exhibiting a well‐defined Arrhenius behavior. Modified Arrhenius expressions for the reaction rate constants both in forward and reverse directions and Evans–Polanyi relationship between the activation and reaction energies have been generated and proposed for kinetic combustion models. The H abstractions by O2 forming the resonantly stabilized radicals were concluded to likely contribute to the initiation of oxidation of the unsaturated C3–C5 species produced in the pyrolysis of the important components of jet fuels.